Processos carioevolutivos na ordem tetraodontiformes: uma visão através de suas diferentes linhagens - Martinez, Pablo Ariel (2010)
Given the great diversity of fishes, the Order Tetraodontiformes stands to show genetic and morphological characteristics enough singular. The fishes of this order have a compact DNA which favors molecular studies, as well as comparisons with more basal species. Model of genome evolution, there are still many gaps in knowledge about their chromosomal patterns and how evolutionary rearrangements influence the marked variation in DNA content of this order. In view of this, we present cytogenetic analyzes of the species Acanthostracion quadricornis (Ostraciidae), A. polygonius (Ostraciidae) Melichthys niger (Balistidae) Cantherhines macrocerus (Monacanthidae) and C. pullus (Monacanthidae), Lagocephalus laevigatus, Colomesus psittacus and Canthigaster figueiredoi (Tetraodontidae), to contribute with cytogenetic data for this group. The analysis was performed by C-banding, Ag-RONs, coloring with base-specific fluorochromes DAPI-CMA3, restriction enzymes AluI, EcoRI, TaqI, PstI and HinfI and in situ hybridization with probes for ribosomal DNA 18S and 5S. The heterochromatic ultrastructure of A. quadricornis and A. polygonius revealed a outstanding heterochromatin content, which may indicate that the accumulation or loss of extensive heterochromatin content could be responsible for large variations in genomic content displayed in different Tetraodontiformes families. The species Cantherhines macrocerus, C. pullus (Monacanthidae) and Melichthys niger (Balistidae) shows a huge karyotypic similarity both numerically and structural. L. laevigatus showed similar cytogenetic features (2n = 44 and single RONs) to the species of the genus Takifugu, which reinforces the idea of their phylogenetic relationships. C. psittacus presented the highest diploid number described for the family (2n = 56) and large amount of HC, features that related with its sister family Diodontidae. Cytogenetic analysis in C. figueiredoi revealed heterochromatic polymorphisms, RONs multiple and Bs chromosomes. These events are rare in marine fishes, and are possibly associated with the strong restructuring and genomic reduction that this family has been suffered. These features, plus the morphological and molecular data suggests that these species share the same ancestral branch, with a possible monophyletic origin. In this study, new contributions to the knowledge of evolutionary patterns facing by Tetraodontiformes are provided and discussed under cytotaxonomyc, genomic and evolutionary perspectives.